TEORI FRAUD PENTAGON: PERAN DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN (STUDI PADA PERUSAHAAN SEKTOR KEUANGAN TAHUN 2018-2020) - Hesti Oktaviani; Dyah Febriantina Istiqomah (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study aims to analyze the effect of the fraud pentagon theory element on fraudulent financial statements in financial sector companies listed on the Indonesia Stock Exchange (IDX). Elements of the pentagon deception theory cannot be analyzed directly, but through proxies. Pressure is proxied by financial targets and external pressures. Opportunity is proxied by ineffective oversight. Rationalization is proxied by auditor turnover. Competence is proxied by the change of director. Arrogance is represented by the CEO's photo frequency. This type of research is quantitative because the data used are in the form of numbers, namely the annual financial report. The sample of this research is 54 financial sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020 obtained by purposive sampling method. The data analysis method used is logistic regression through SPSS version 26. The results show that the elements of pressure and opportunity affect fraudulent financial statements. While the elements of rationalization, competence and arrogance have no effect on fraudulent financial statements.